Unexpected Tc-99m labelled erythrocyte scintigraphy finding of a patient with suspicion of active bleeding into renal haematoma - Koç, Zehra Pinar; Balci, Tansel Ansal; Çeliker, Hüseyin (BMJ Publishing Group, 2011)
A 36-year-old male patient with suspicion of active bleeding into renal haematoma loge was sent to our clinic for Tc-99m labelled erythrocyte scintigraphy. Scintigraphy showed no active bleeding to renal haematoma but coexisting active haemorrhage of stomach which was confirmed as erosive bulbitis with further endoscopy.
Keywords: erythrocyte tc 99m; hemoglobin; adult; article; case report; computer assisted tomography; differential diagnosis; erosion; erosive bulbitis; flank pain; gastrointestinal endoscopy; gastrointestinal tract scintiscanning; hematoma; hemodialysis; hemoglobin blood level; hiatus hernia; human; kidney hematoma; kidney hemorrhage; male; peritonitis; priority journal; stomach hemorrhage